Mergers When Prices Are Negotiated: Evidence from the Hospital Industry - Gowrisankaran, Gautam; Nevo, Aviv; Town, Robert (American Economic Review, 2015)
We estimate a bargaining model of competition between hospitals and managed care organizations (MCOs) and use the estimates to evaluate the effects of hospital mergers. We find that MCO bargaining restrains hospital prices significantly. The model demonstrates the potential impact of coinsurance rates, which allow MCOs to partly steer patients toward cheaper hospitals. We show that increasing patient coinsurance tenfold would reduce prices by 16 percent. We find that a proposed hospital acquisition in Northern Virginia that was challenged by the Federal Trade Commission would have significantly raised hospital prices. Remedies based on separate bargaining do not alleviate the price increases. (JEL C78, G34, I11, I13, L13)